THE INFLUENCE OF ENTREPRENEURIAL CHARACTERISTICS AND SELF-EFFICACY AS MEDIATORS ON ENTREPRENEURIAL INTENTION ON TARUMANAGARA UNIVERSITY STUDENTS - Malvin Sufianto; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2026)
One of the biggest problems that every country must face is unemployment. In Indonesia, the unemployment rate in February 2024 was 4.82%. One way to address the unemployment problem is to increase awareness of entrepreneurial knowledge and encourage the creation of new businesses, which will indirectly create jobs. Based on this, this study aims to examine the effect of entrepreneurial knowledge, mindset, and creativity on entrepreneurial intentions, with self-efficacy as a mediating variable, in Tarumanagara University students. The research sample consisted of 160 students majoring in economics. Data processing was carried out using the SmartPLS program. The results of the study indicate that: entrepreneurial knowledge has a positive and significant effect on mindset, entrepreneurial knowledge, mindset, and creativity have a positive and significant effect on entrepreneurial intentions, self-efficacy has a positive, but not significant, effect in mediating the relationship between entrepreneurial knowledge, mindset, and creativity with entrepreneurial intentions.